Quantitative and qualitative analysis of bioaerosols emissions from the domestic eastern wastewater treatment plant, Alexandria, Egypt - Ebtesam El-Bestawy; Mohammed Mahmoud Ibrahim; El sayed Ahmed Shalaby (Scientific Reports)
Abstract Bioaerosol studies showed that wastewater treatment plants (WWTPs) are a significant source of bioaerosol emissions. In this study, 170 samples of total bacteria, total coliform, and total fungi were collected from 10 sites within a domestic WWTP, Alexandria, Egypt, using the sedimentation technique. According to the Index of Microbial Air Contamination (IMA) classes, the total bacteria range was 108–5120 CFU/dm2/hour, and all samples were classified as “very poor” except one sample of an office, which was classified as “poor.” The total coliform range was 0–565 CFU/dm2/hour, and 6 samples were classified as “very poor,” while one sample was classified as “poor.” The total fungi range was 0–209 CFU/dm2/hour, and 9 samples were classified as “very poor,” while 4 samples were classified as “poor.” After the conversion to CFU/m3, the counts of total bacteria, total coliforms, and total fungi were 897 − 42.7 × 103, 0–4.71 × 103, and 0–2.69 × 103 CFU/m3, respectively. Several identified bioaerosols have been reported before as a cause of human infections. They included Lysinibacillus fusiformis, Bacillus cereus, Alcaligenes faecalis, Klebsiella sp., Escherichia coli, Aspergillus spp., Penicillium spp., Rhizopus sp., Candida sp., and Rhodotorula sp. These results indicated an increased health risk to WWTP staff, which needs more attention and more efficient control measures.